The artificial intelligence, a challenge in the field of health - López, Indira (2024)
The advancement of technology has rapidly transformed society, especially in the field of healthcare, where artificial intelligence has aroused great interest due to its various applications. Several areas, including health sciences, that utilize these systems have considered it essential to incorporate these tools into their field. Thus, over the decades, artificial intelligence has been used in medicine, from interpreting electrocardiograms to analyzing large datasets for diagnoses, treatments, and guiding public policies. In the field of medical sciences, two main branches of application are identified: a physical one, which supports medical personnel in patient care, and a virtual one, which focuses on research and public health. Although artificial intelligence can alleviate the burden on healthcare staff, it poses risks such as the loss of direct contact between doctors and patients, as well as ethical dilemmas regarding the privacy of health data, making it essential to continuously evaluate its implementation and reflect on its ethical and social implications. While its benefits are acknowledged, it is crucial to critically address its potential impacts and ethical concerns.